From structure topology to chemical composition. III. Titanium silicates : the Crystal chemistry of barytolamprophyllite - E. Sokolova; F. Cámara (The Canadian Mineralogist, 2008)
The crystal structure of barytolamprophyllite, ideally (BaK) Na3 Ti3 (Si2O7)2O2 (OH)2, a 19.8971(7), b 7.1165(3), c 5.4108(2) Å, β 96.676(2)°, V 760.96(3) Å3, space group C2/m, Z = 2, Dcalc. 3.521 g.cm-3, from Mt. Yuksporr, Khibina alkaline massif, Kola Peninsula, Russia, has been refined to R1 = 2.82% on the basis of 1175 unique reflections (Fo > 4σF) collected on a Bruker AXS SMART APEX diffractometer with a CCD detector and MoKα radiation. An electron-microprobe analysis gave (wt.%): SiO2 29.31, Al2O3 0.16. Nb2O5 0.11, TiO2 28.39, Fe2O3 0.49, FeO 2.66, MnO 2.42, MgO 0.26, CaO 0.88, SrO 4.11, BaO 16.37, K2O 3.52, Na2O 7.90, F 1.69, H2O 0.77 (calculated from structure refinement), O=F -0.71,for a total of 98.33. The empirical formula is (Ba0.88 K0.61 Sr0.33 Ca0.05 □0.13) Σ2.00 (Na2.09 Fe2+0.30 Mn2+ 0.28 Ca0.08 Mg0.05 □ 0.20) Σ3.00 (Ti2.91 Fe3+0.05 Al0.03 Nb0.01) Σ3.00 (Si2O7)2 O2 [F0.73 (OH)0.70 O0.57] Σ2.00 Z = 2, calculated on the basis of 4 Si apfu. The crystal structure of barytolamprophyllite can be described as a combination of two blocks, a TS (titanium silicate) block and an I (intermediate) block. The TS block consists of HOH sheets (H heteropolyhedral, O octahedral), which occur in 24 Ti disilicate minerals. In the TS block, there are six cation sites, a [4]-coordinated Si site with <Si-O> = 1.631 Å, two Ti-dominant sites, the [5]-coordinated MH site and [6]-coordinated M°(1) site, and two [6]-coordinated Na-dominant sites, M°(2) and M°(3). The MH site (= Ti1.97 Al0.03 pfu) is coordinated by five O atoms, with <MH-O> = 1.914 Å; the M°(1) site (= Ti0.94 Fe3+ 0.05 Nb0.01 pfu) is coordinated by four O atoms and two OH groups, with <M°(1)-O> = 1.993 Å; the M°(2) and M°(3) sites (= Na1.00 and Na1.09 Fe2+0.30 Mn2+0.28 Ca0.08 Mg0.05 □0.20 pfu, respectively) are coordinated by six O atoms with <M°(2)-O> = 2.441 Å, and four O atoms and two OH groups, with <M°(3)-O> = 2.296 Å, respectively. The MH square pyramid and (Si2O7) groups constitute the H sheet. The M°(1-3) ...